KINETIC OF EXCITATION OF HETERONUCLEAR IONIC MOLECULES (ArXe) + BY HARD IONISER - Khasenov, M. U. (Recent Contributions to Physics, 2009)
The opportunity of use of the emission with λ ~329 nm in Ar-Xe mixtures in radioisotope light sources is investigated. At excitation by a-particles in this mixture the transitions from Ar+ (2 P1/2)Xe state (λ ~329 nm and ~508 nm) are observed only and there are no transitions from Ar+(2P3/2)Xe. At use of α-sources helium collects, dependence of intensity of emission in a band of 329 nm from pressure of helium in mixture Ar-XeHe is also investigated.
Keywords: light